4-(trifluormetil)haloquinolinas: síntese, reações de acoplamento cruzado C-C e C-N, propriedades fotoluminescentes e antimicrobianas - Rodrigues, Melissa Budke (2018)
In this thesis, methodologies were developed in order to obtain novel trifluormethyl substituted quinolines through intramolecular cyclocondensation reactions with subsequent C-C and C-N cross coupling of the Sonogashira, Buchwald-Hartwig and Ullmann type using phenylacetylene, morpholine, pyrrolidine and indole as precursors. Its electronic and structural properties were investigated by mass spectrometry, absorption and emission spectroscopy (photoluminescence), nuclear magnetic resonance of 1H and 13C, besides studies involving interaction with DNA and evaluation of possible antimicrobial properties. Initially, a series of 1-(1-((3-chloro-4-fluorophenyl)amino)-3,4-dihydronaphthalen-2-yl)-2,2,2-trifluoroethan-1-one (2a), (Z)-4-((3-chloro-4-fluorophenyl)amino)-1,1,1-trifluoro-3-alken-2-ones (2b-g) and (Z)-4-((4-bromophenyl)amino)-1,1,1-trifluoro-3-alken-2-ones (3b-j) were obtained utilizing the precursors 3-chloro-4-fluoro-aniline, 4-bromo-aniline and 4-alkoxi-4-alkil[aryl(heteroaryl)]-1,1,1-trifluoro-3-alken-2-ones (1a-j) (R = CH3, C6H5, 4-FC6H4, 4-BrC6H4, 4-CH3C6H4, 4-CF3C6H4, 2-furyl, 2-thienyl). Lastly, the enaminoketones compounds 2 and 3 were subjected to regiosselective intramolecular cyclization in sulfuric acid, resulting in 7-chloro-6-fluoro-4-(trifluoromethyl)quinolines (4) and 6-bromo-4-(trifluoromethyl)quinolines (5) in good yields (65 – 90%). Subsequently, C-C coupling reactions were performed in the quinolinic systems 4 and 5, where it was possible to obtain novel compounds 6-fluoro-7-(phenylethynyl)-4-(trifluoromethyl)quinolines (6) and 6-(phenylethynyl)-4-(trifluoromethyl)quinolines (7) in good yields (25 – 88%) through the Sonogashira coupling reaction using phenylacethylene as one of the precursors. Using the quinolines 5 together, as precursors, with the morpholine and pyrrolidine, it was possible to perform Buchwald-Hartwig coupling reactions, promoting the formation of new C-N bond. Thus, novel compounds 4-(4-(trifluoromethyl)quinolin-6-yl)morpholine (8) and 6-(pyrrolidin-1-yl)-4-(trifluoromethyl)quinolines (9) substituted with R = C6H5, 4-FC6H4, 4-CH3C6H4, 4-CF3C6H4, 2-thienyl were obtained in yields of 60 – 88%. Subsequently, the Ullmann coupling reaction catalyzed for CuI and DMEDA from the 6-bromo-quinolines (5) and indole, led in to obtaining a new series of five compounds 6-(1H-indol-1-yl)-4-(trifluoromethyl)quinolines (10) (R = C6H5, 4-FC6H4, 4-CH3C6H4, 4-CF3C6H4, 2-thienyl) with yields of 57 – 84%. The evaluation of photoluminescent properties of the quinolines 8 and 9 demonstrated that the compounds showed fuorescence in the region of blue for cyan, with moderated quantum yields in the 400 – 700 nm regions. In DNA interaction studies, the compounds showed strong ct-DNA bonding, especially the compounds substituted with morpholine at the 6-position of the quinolinic ring. The compounds 4-10 were evaluated against four types of bacterias and six types of fungi, but these were not active against the microorganism used. Further tests involving other types of bacterias and fungi should be performed to better evaluate the micro- and micobiologic properties of these novel 4-trifluoromethyl-quinolines.